Peran Sistem Informasi Fungsional Dalam Meningkatkan Efesiensi dan Pengambilan Keputusan Organisasi di Era Digital - Narach Larasati Nasution; Nur Azizaini Zhaharah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aimed to analyze the role of functional information systems in improving operational efficiency and supporting organizational decision-making in the digital era. The study used a descriptive qualitative approach with a literature study method based on journals, books, and relevant academic sources. The results showed that functional information systems were able to improve operational efficiency through work process automation, faster data processing, reduced recording errors, and better organizational coordination. In addition, the system produced accurate and relevant information that supported more effective and data-based decision-making. The success of system implementation was influenced by system suitability, system integration, and human resource competence. However, the implementation still faced challenges such as low digital literacy and the limited use of organizational data. Therefore, organizations needed to develop integrated information systems to improve work effectiveness and organizational competitiveness in the digital era.